Molecular dynamics simulations of ch4 clathrate hydrate dissociation adjacent to hydrated silica surfaces - Bagherzadeh, A.; Englezos, Peter; Alavi, S.; Kumar, Rajnish; Ripmeester, John A. (7th International Conference on Gas Hydrates, 2011)
We use molecular dynamics simulations to study the decomposition of structure I CH4 clathrate hydrate exposed to water. Simulations are performed for a hydrate + water system and two related cases with the hydrate adjacent to hydrate silica layers. The simulations are in the NVE adiabatic ensemble paying careful attention to the non-isothermal nature of the hydrate dissociation process. The effects of mass and energy transfer on the hydrate dissociation rate are studied. The effect of the silica surface on the dissociation rate and mechanism are studied. It is observed that the hydrate layer decomposes more quickly in simulations where it is in contact with silica. The implications on decomposition of the hydrate in hydrate reservoirs adjacent to sand sediments are discussed.

Review of the hydrate based gas separation (HBGS) process for carbon dioxide pre-combustion capture - Babu, Ponnivalavan; Linga, Praveen; Kumar, Rajnish; Englezos, Peter (Energy, 2015)
In this work, a systematic review of the literature work done so far on the use of hydrate crystallization as a basis to develop data for the hydrate based gas separation (HBGS) process for the capture of CO2 from fuel gas mixtures is presented. Such a gas mixture may arise in integrated gasification combined cycle (IGCC) power plants. A thorough assessment of the thermodynamic, kinetic factors and economic aspects of the HBGS process and critical comments are presented. Compared with competing technologies, high CO2 capacity and the use of water as a solvent are key advantages for the HBGS process for CO2 capture. Furthermore, in this review, a snapshot of the current state-of-the-art is presented and further research and development opportunities and pathways for commercializing the HBGS process for pre-combustion capture of CO2 from IGCC power plants are discussed. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Gas separation; IGCC plants; Pre-combustion capture